A V log V algorithm for isomorphism of triconnected planar graphs - Hopcroft, J.E.; Tarjan, R.E. (Journal of computer and system sciences, 1973)
An algorithm for determining whether two triconnected planar graphs are isomorphic is presented. The asymptotic growth rate of the algorithm is bounded by a constant times | V| log | V| where | V| is the number of vertices in the graphs.